KOMPOSISI HASIL TANGKAPAN GILLNET MILENIUM BERDASARKAN PERBEDAAN KEDALAMAN SETTING DIPERAIRAN PULAU AMBON - Muhidin Syamsuddin; Haruna Haruna; Indra Cahya; Selfi Sangadji (Universitas Pattimura, 2024)
The natural dynamics of the distribution of fish resources in marine waters are not uniform. This will have implications for optimizing the utilization of fish resources using various fishing gear in a fishing area. Fishing using millennium gillnets is generally not done by many fishermen on Ambon Island. The research aimed to determine the composition and influence of differences in millennium gillnet depth on catch results. This research method is a fishing experiment using 3 units of 3.5-inch millennium gillnets of uniform size which are set on the bottom of the water at treatment depths, namely 0-20 meters, 21-40 meters and > 40 meters. Simultaneous capture operations in the afternoon for 8 capture attempts. During the research, the catch was 364 fish weighing 209 kg. 6 types of fish were identified, namely Kuwe (Caranx sexfasciatus), yellow-tailed Lalosi (Caesio cunning), sand porter (Naso thynnoides), Samandar (Siganus sp), and grouper (Epinephelus merra), and mackerel (Scomberomorus gullatus). This type of fish is usually found swimming in open water or near the sea surface. The highest number of catches was the Kuwe fish species, 135 fish (37.09%) weighing 56.4 kg (26.99%), the lowest was the Tenggiri fish species (Scomberomorus gullatus), 5 fish (1.37%) weighing 5.1 kg (2, 44%). The highest catch was in the 21-40 m depth range, namely 162 fish and 94.7 kg, followed by more than 41 m, namely 103 fish and 57 kg, and the lowest in the 0-20 m depth range, namely 99 fish and 57.3 kg. The chance of catching fish occurs at all net-setting depths, but the highest chance occurs at 21-40 m. The results of the analysis showed that neither the overall catch nor the dominant fish species showed significant differences based on differences in depth.